Earliest photograph of Athabasca and Dome Glaciers, Alberta - Luckman, Brian; Kavanagh, Trudy; Craig, Ian; St. George, R. (Géographie physique et Quaternaire, 1999)
AbstractA digitally enhanced copy of the first photograph showing Athabasca and Dome Glacier is presented and compared with a similar view taken in 1998. The photograph, taken by Mary Schäffer, appears to date from 1906 based on contextual evidence from her journals and the image. Changes in the glacier extent and vegetation cover during the present century are discussed briefly.